New Science of Learning
XXXIV, 607 p.
Keywords: The earliest educational software simply transferred print material from the page to the monitor. Since then, the Internet and other digital media have brought students an ever-expanding, low-cost knowledge base and the opportunity to interact with minds around the globe—while running the risk of shortening their attention spans, isolating them from interpersonal contact, and subjecting them to information overload. The New Science of Learning: Cognition, Computers and Collaboration in Education deftly explores the multiple relationships found among these critical elements in students’ increasingly complex and multi-paced educational experience. Starting with instructors’ insights into the cognitive effects of digital media—a diverse range of viewpoints with little consensus—this cutting-edge resource acknowledges the double-edged potential inherent in computer-based education and its role in shaping students’ thinking capabilities. Accordingly, the emphasis is on strategies that maximize the strengths and compensate for the negative aspects of digital learning, including: Group cognition as a foundation for learning Metacognitive control of learning and remembering Higher education course development using open education resources Designing a technology-oriented teacher professional development model Supporting student collaboration with digital video tools Teaching and learning through social annotation practices The New Science of Learning: Cognition, Computers and Collaboration in Education brings emerging challenges and innovative ideas into sharp focus for researchers in educational psychology, instructional design, education technologies, and the learning sciences. Endorsements: "The book brings together leadingresearchers who study how technology can enhance student learning. They address questions of how technology can support collaborative learning, knowledge building, assessment, metacognition, and professional development. For example, a chapter by Howard Gardner and his colleagues describes how students are changing as they grow up with new technologies, and a chapter by Kurt W. Fischer and his colleagues describes redesigning testing with the use of latest in computer technology and learning science. Altogether it is a fine collection of chapters about the latest advances in educational technology." Allan Collins, Northwestern University – Author, Rethinking Education in the Age of Technology "Modern learning technologies have emerged in the 21st century as powerful tools to enhance learning and thinking, but much of their potential remains to be realized. Remarkably, as we explore how learners interact with diverse learning environments, including digital media, we are discovering that these tools also are revealing new insights into how our minds operate and how better to realize the promise that learning technologies offer. This book presents some of the latest discoveries and theoretical insights about how we think and learn, especially through explorations employing digital media. This is a first-class book containing chapters by some of the best researchers worldwide." O. R. Anderson, Columbia University, Teachers College – Chair, Mathematics, Science and Technology.